PENGGUNAAN SAKSI VERBALISAN PADA PEMBUKTIAN PERKARA PENCURIAN DALAM KEADAAN YANG MEMBERATKAN - Iskawati, Novita; Mahadewi, Putri (Verstek, 2023)
This article analyzes the use of verbal witnesses at proving the case of theft in a situation that burdens the Decision Number 45/Pid.B/2021/PN Wng. The purpose of this article was to determine the compatibility between the use of verbal witness thereof theft in a situation that burdens the provisions of Law Number 8 of 1981 concerning Law of the Criminal Procedure or Book of the Crime Law of the Crime Event (KUHAP). This writing uses normative legal research methods that are prescriptive and applied with a case approach. The type of legal material used is primary and secondary legal material, in terms of document literature studies or literature, and techniques for legal material analysis using the deductive cylogism method. The results showed that the compatibility of the use of verbal witnesses in proving the case of theft in a situation that burdens in Decision Number 45/Pid.B/2021/PN Wng with KUHAP based on the provisions of Article 163 KUHAP where the witness’s information at the trial is different from investigation report, so the chairman of the panel of judges can ask information about the difference, in this case the judge asked to present verbal witness and the position of verbal witness in proving the error more to complementary evidence that doesn’t stand alone and become clue evidence in accordance the Article 184 KUHAP.Keywords: Clue; Proving; Verbal Witness.